2016
DOI: 10.1371/journal.pone.0146394
|View full text |Cite
|
Sign up to set email alerts
|

Implications for Welfare, Productivity and Sustainability of the Variation in Reported Levels of Mortality for Laying Hen Flocks Kept in Different Housing Systems: A Meta-Analysis of Ten Studies

Abstract: Data from ten sources comprising 3,851 flocks were modelled to identify variation in levels of mortality in laying hens. The predicted increase with age was curvilinear with significant variation between the seven breed categories. Mortality was higher in loose housing systems than in cages and variable within system, confirming previous reports. Cumulative mortality (CM) was higher in flocks with intact beaks (χ2 = 6.03; df 1; p = 0.014) than in those with trimmed beaks. Most data were available for free-rang… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
59
0
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 71 publications
(64 citation statements)
references
References 22 publications
2
59
0
2
Order By: Relevance
“…Access to an outdoor range reduces the risk of feather pecking behaviour (Green et al 2000;Lambton et al 2010) and may provide further opportunity to fulfil behavioural needs such as foraging and dustbathing (Weeks and Nicol 2006). However, range use is often low (Pettersson et al 2016b) and mortality and injurious pecking behaviour are generally at higher levels than recorded in cage systems (Sherwin et al 2010;Weeks et al 2016).…”
Section: Introductionmentioning
confidence: 99%
“…Access to an outdoor range reduces the risk of feather pecking behaviour (Green et al 2000;Lambton et al 2010) and may provide further opportunity to fulfil behavioural needs such as foraging and dustbathing (Weeks and Nicol 2006). However, range use is often low (Pettersson et al 2016b) and mortality and injurious pecking behaviour are generally at higher levels than recorded in cage systems (Sherwin et al 2010;Weeks et al 2016).…”
Section: Introductionmentioning
confidence: 99%
“…Free-range hens are exposed to more environmental stressors, such as extreme weather conditions, predation, exposure to wild birds, and aggression, in comparison with hens from barn and cage systems (2)(3)(4). The findings from a recent Australian survey revealed that free-range egg producers imputed financial losses to heat stress, cannibalism, grass impaction, diseases, and malnutrition (5).…”
mentioning
confidence: 99%
“…Feather pecking and cannibalism are major causes of feather loss, poor welfare, and higher mortality, which are mitigated by the highly controversial practice of beak trimming in many management systems. A recent analysis of data from 3500 commercial flocks in the EU indicated that mortality rates were significantly higher and considerably more variable in non-cage and especially in free-range systems compared to cage systems [89]. In that study, genetic strain of the hen was a significant factor and risks were considerably greater when hens were not beak trimmed.…”
Section: Welfare Trade-offs Related To Different Laying Hen Housing Smentioning
confidence: 84%
“…Several literature reviews and scientific reports have summarized findings from studies comparing the welfare of hens in different housing systems [81][82][83][84], including reports comparing various welfare indicators collected on large-scale commercial farms [85][86][87][88][89]. Generally, all these reports indicate significant trade-offs for different aspects of welfare for hens in different housing systems.…”
Section: Welfare Trade-offs Related To Different Laying Hen Housing Smentioning
confidence: 99%
See 1 more Smart Citation